Reduced striatal dopamine release during motor skill acquisition in Parkinson's disease. - Shoji Kawashima; Yoshino Ueki; Takashi Kato; Kengo Ito; Noriyuki Matsukawa (PLoS ONE, 2018)
Striatal dopamine is functionally important for the acquisition of motor skills. However, it remains controversial as to whether intrinsic processing of motor learning is impaired in patients with Parkinson's disease (PD), and if yes, whether the impairment is associated with altered striatal dopamine release. Additionally, most neuro-imaging studies of patients with PD have focused on motor sequence learning. In contrast, skill acquisition, specifically, the reconstruction of muscle control of isolated movements, has barely been studied.In this study, we used a repetitive skill training task to measure the peak acceleration of left thumb movement during a process to achieve fine tuning of motor skill. Using 11C-raclopride (RAC) positron emission tomography, we investigated changes in striatal dopamine levels in two conditions of a skill acquisition task: initial skill training (Day 1) and acquired condition (Day 2) with eight patients with PD and age-matched healthy subjects (HS).In HS, the mean acceleration of each session improved through repeated training sessions on Day 1. However, in patients with PD, the training-associated increase was less than that for HS, and this suggests that repetitive skill training does not result in the effective improvement of motor performance. The regions of interest (ROI) analysis revealed that the RAC-binding potential (BP) was significantly reduced in the right putamen on Day 1 compared with Day 2 in HS. In patients with PD, BP within the right putamen was unchanged. Further, we found that patients with PD had increased dopamine levels within the right ventral striatum (VST) and right caudate (CAU) on Day 2, which was greater than that in HS. These results suggest the impaired activation of the putamen during skill acquisition in patients with PD and compensated hyperactivation of the VST and CAU for the reduced dopamine release within the dorsal putamen (DPU).Our findings suggest that patients with PD had insufficiency in the process to improve motor skills. Different patterns of striatal dopamine release are relevant to the impairment of these motor functions in patients with PD, at the early stage of the disease.